THE IMPACT OF ELECTRONIC ISSUANCE OF RECEIPTS FOR FEES IN THE SCHOOL TEACHERS’ PROFESSIONAL ACCOUNTING - Vergara Moncada, Raúl Jesús (2012)
Currently, in almost all of the Tax Administrations under the structure of American Center of Tax Administration (CIAT) are in an extensive development of the first electronic age with the voluntary use of spreadsheets, then with the Electronic Program Book (PLE), new formats of books and records related to tax matters, and recently with electronic invoices. The Peruvian case is no stranger to the National Superintendence of Tax Administration (SUNAT), which has implemented for the time being in a volunteer manner. Thus, the aim of this investigative work is to determine to what extent this new scanning system impacts the professionals who work in the School of Accounting of San Marcos. Hoping more teachers use this system and simplifying the administrative system would contribute to preserving our environment since this would prevent an increase on paper production and thus counterbalance the indiscriminate cutting of trees in this country.